2016
DOI: 10.3389/fnsyn.2016.00033
|View full text |Cite
|
Sign up to set email alerts
|

Afferent Input Selects NMDA Receptor Subtype to Determine the Persistency of Hippocampal LTP in Freely Behaving Mice

Abstract: The glutamatergic N-methyl-D-aspartate receptor (NMDAR) is critically involved in many forms of hippocampus-dependent memory that may be enabled by synaptic plasticity. Behavioral studies with NMDAR antagonists and NMDAR subunit (GluN2) mutants revealed distinct contributions from GluN2A- and GluN2B-containing NMDARs to rapidly and slowly acquired memory performance. Furthermore, studies of synaptic plasticity, in genetically modified mice in vitro, suggest that GluN2A and GluN2B may contribute in different wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 90 publications
(120 reference statements)
1
40
0
Order By: Relevance
“…Thus, the slowly developing potentiation that we observed following repeated applications of HFS to the perforant path of wild‐type animals in this study may have recruited NMDA receptors that contain GluN2B and/or L‐type voltage‐gated calcium channels. This likelihood is confirmed by the absence of an early phase of LTP in knockout animals: both NMDA receptors (Ballesteros et al, ) and L‐type voltage‐gated calcium channels (Manahan‐Vaughan et al, ) are required for the induction phase of LTP in vivo. Despite the significantly reduced mRNA expression of GluN2B and Ca v 1.3 in the dentate gyrus of knockout mice, a slowly developing LTP was induced by repeated applications of HFS.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Thus, the slowly developing potentiation that we observed following repeated applications of HFS to the perforant path of wild‐type animals in this study may have recruited NMDA receptors that contain GluN2B and/or L‐type voltage‐gated calcium channels. This likelihood is confirmed by the absence of an early phase of LTP in knockout animals: both NMDA receptors (Ballesteros et al, ) and L‐type voltage‐gated calcium channels (Manahan‐Vaughan et al, ) are required for the induction phase of LTP in vivo. Despite the significantly reduced mRNA expression of GluN2B and Ca v 1.3 in the dentate gyrus of knockout mice, a slowly developing LTP was induced by repeated applications of HFS.…”
Section: Discussionmentioning
confidence: 91%
“…In freely behaving rats, very strong tetanic stimulation induces a form of LTP that predominantly depends on activation of L‐type voltage gated calcium channels (Ca v 1.3) (Manahan‐Vaughan et al, ), a property that has also been reported in vitro (Grover & Teyler, ), and mice that lack tenascin C also show deficits in this form of LTP (Evers et al, ). In freely behaving mice, the dependency of LTP in the CA1 region is tightly correlated to the afferent stimulation pattern, whereby late (>24 hr) LTP, that is induced by repetitive HFS, requires activation of NMDA receptors that contain GluN2B (Ballesteros et al, ). By contrast, short‐lasting LTP that is induced with milder stimulation patterns requires activation of GluN2A and not GluN2B receptors (Ballesteros et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanistically, such differences, in the magnitude of potentiation, may be related to the differential expression of plasticity‐related receptors that we detected along the dorsoventral hippocampal axis as well as to reported differences in ion channel expression. In vivo , GluN2A‐containing NMDARs are important for the induction of the early phase of LTP (E‐LTP, < 1 h), whereas activation of GluN1/GluN2B‐containing NMDARs appear more important for LTP that lasts for longer periods (Ballesteros, Buschler, Köhr, & Manahan‐Vaughan, ). GluN1/GluN2B‐containing receptors also require a higher membrane depolarization for their activation compared with GluN1/GluN2A‐containing receptors (Clarke, Glasgoq, & Johnson, ).…”
Section: Discussionmentioning
confidence: 99%